محمد عبد الرضا جاسم الدوخي تاثير النحاس على اسجة غلاصم يافعات اسماك البني - عبد الرضا, محمد (University of Thi-Qar Journal of Science, 2019)
Gill structure of Barbus sharpeyi (Gunther) juveniles has beenstudied, they were exposed to various concentrations of copper. Gilldamage resulting from exposure to sub lethal concentrations.Histological changes in the gills included hyperplasia of the gill tissue,some engorgement with bleeding in the secondary lamellae, epithelialseparation, necrosis, and fusion of adjacent secondary lamellae. Theresult of experiment shows that the behavior of susceptible fishes tohigh concentration(3ppm) after 3 hr. of exposure to the ion, startingwith swimming close to water surface circulation movement andhemorrhage in gill lamella.